Enterprise Performance in Nepal: Evidence on Migration, Grants, and Business Development Support from Palungtar Municipality - Devkota, Ram Mani (Journal of Development and Administrative Studies, 2025)
In Nepal, enterprise development is a very important factor in livelihood diversification and local economic resilience especially where labor migration and decentralized development planning influence the situation. The paper will be looking at the enterprise performance in Palungtar Municipality, Nepal, and will look at the contribution of the context of migration, grants, and business development support. The analysis will consider three major outcomes including the business growth, annual enterprise revenue, and enterprise resilience using cross-sectional data on a field survey of 185 enterprises, which has taken place in 2025. The models used were multivariate regression and logistic regression to business growth and ordinary least squares (OLS) regression with robust standard errors to revenue and resilience outcomes. The findings show that enterprise characteristics and program support variables did not have significance in short-term business growth. Consequently, women-led businesses, education level, and overall business development plan had significant and positive links with increased annual business revenue. There was a negative correlation between training completion and revenue, and this could be because of some targeting effect or a delayed return on capacity-building interventions. Statistically significant determinants of enterprise resilience were not established, suggesting that resilience can be influenced by macro-dynamics of the household and community that are not tied to enterprise-level aspects. The study provides available evidence on entrepreneurs at the municipality level by combining the context of migration with the analysis of enterprise support and provides policy-relevant information to develop inclusive and resilience-focused enterprise development policies in Nepal.